Disaster Preparedness Strategies in the Kathmandu Valley (Patan Prospective Journal, 2025)
This paper examines the impact of the disasters including earthquake and floods on the residents of the Kathmandu Valley. This study aims to assess preparedness strategies based on the secondary data gathered from the sources including reports and studies. The Kathmandu Valley is extremely susceptible to various natural hazards, especially earthquakes, floods, and landslides. This study examines available literature, policy reports, and program assessments to combine effective disaster readiness approaches suited to the Valley’s socio-economic, geographic, and administrative conditions. Employing a systematic literature review approach, the research highlights five key preparedness areas: governance and planning, land use and infrastructure informed by hazards, community-based preparedness and capacity enhancement, early warning and communication mechanisms, and simulations, drills, and logistical support. The article concludes with practical suggestions for local and regional authorities, community groups, and global partners to enhance resilience and minimize disaster risk. Besides, the role of community in getting aware and taking precautions to fight against natural hazards becomes crucial in terms of mitigating the risk and minimizes the consequences of the disasters.